Caracterización Del Proceso De Producción De Tableros Alistonados En Pereira Y Dosquebradas (2019)
From a research project registered in the UCPR Research Center, this article presents the study results on current techniques in the  manufacturing process of edge-glued panels, as well as the technology used for the wood and furniture regional industry in the handling and disposal of the wood laths (raw material) and edge-glued panels. In addition, it is analyzed a different way of working with wood as an alternative for the regional industry, considering that not only adequate mechanical properties are achieved, which are higher than normal wood, but also itis possible to provide aesthetic value of wood products.